Answer:
g'(10) =
![(-1)/(16)](https://img.qammunity.org/2020/formulas/physics/middle-school/bomosptk9nb2832jwchw528p21aw156tv2.png)
Step-by-step explanation:
Since g is the inverse of f ,
We can write
g(f(x)) = x (Identity)
Differentiating both sides of the equation we get,
g'(f(x)).f'(x) = 1
g'(10) =
--equation[1] Where f(x) = 10
Now, we have to find x when f(x) = 10
Thus 10 =
+ 2
= 8
x =
![(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ybjkeso7qr5r7js5h0mv9de35dih0sxfpl.png)
Since f(x) =
+ 2
f'(x) = -
![(4)/(x^(2) )](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t4mtkcaqf9mmxr4qposrww0dzk3az3ivkv.png)
f'(
) = -4 × 4 = -16
Putting it in equation 1, we get:
We get g'(10) = -
![(1)/(16)](https://img.qammunity.org/2020/formulas/mathematics/college/2u8ajab962tcjc75axyz4qs8cbip9vgn2b.png)